Framework Administered Account for Selected Fund Activities : United States Subaccount for Selected Fund Activities. (Policy Papers; Policy Paper ;, 2010)
Niger's macroeconomic performance and policies through end-January 2010 were assessed in the IMF Country Report No. 10/146, issued following the completion of the third program review under the arrangement under the Extended Credit Facility (ECF) from the IMF. Since the military intervention in February, the near-term growth outlook has weakened, reflecting the intensity of the food crisis and some contraction in public spending, but the outlook for 2011 is broadly favorable provided that budgetary policies remain appropriately cautious, that normal weather conditions prevail, and that donor support for Niger picks up.